2019
DOI: 10.3390/md17100578
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Sponge-Associated Bacteria from Agelas sventres and Xestospongia muta Collected from Different Depths

Abstract: Sponge-associated bacteria have been mostly cultured from shallow water (≤30 m) sponges, whereas only few studies targeted specimens from below 30 m. This study assessed the cultivability of bacteria from two marine sponges Xestospongia muta and Agelas sventres collected from shallow (<30 m), upper mesophotic (30–60 m), and lower mesophotic (60–90 m) reefs. Sponge-associated bacteria were cultivated on six different media, and replicate plates were used to pick individual colonies or to recover the entire b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 71 publications
(98 reference statements)
0
15
0
2
Order By: Relevance
“…In addition, a previous study on the sponge Xestospongia muta demonstrated that changing NO x concentrations over depth contribute to shaping the microbial community composition (Morrow et al, 2016). Furthermore, several studies have noted that depth is an important factor in structuring sponge-associated microbiomes (Indraningrat et al, 2019;Lesser et al, 2020;Steinert et al, 2016). This is, to our knowledge, the first study that explores the impact of seawater biogeochemistry on deep-sea sponge microbiomes.…”
Section: A Seamount Imprint On Sponge-associated Microbial Communitiesmentioning
confidence: 65%
See 2 more Smart Citations
“…In addition, a previous study on the sponge Xestospongia muta demonstrated that changing NO x concentrations over depth contribute to shaping the microbial community composition (Morrow et al, 2016). Furthermore, several studies have noted that depth is an important factor in structuring sponge-associated microbiomes (Indraningrat et al, 2019;Lesser et al, 2020;Steinert et al, 2016). This is, to our knowledge, the first study that explores the impact of seawater biogeochemistry on deep-sea sponge microbiomes.…”
Section: A Seamount Imprint On Sponge-associated Microbial Communitiesmentioning
confidence: 65%
“…Research records about seamount microbiology are sparse and comparably few studies have been conducted on deepsea sponge microbiomes in general (Borchert et al, 2017;Jackson et al, 2013;Kennedy et al, 2014;Reveillaud et al, 2014). Our main aim was to assess whether and via which potential mechanisms a seamount can affect the community structure of pelagic and benthos (sponge)-associated microbial communities, using the Schulz Bank seamount as an exemplary field site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a previous study on the sponge Xestospongia muta demonstrated that changing NOx concentrations over depth contribute to shaping the microbial community composition (Morrow et al, 2016). Furthermore, several studies have noted that depth is an important factor in structuring sponge-associated microbiomes (Indraningrat et al, 2019;Lesser et al, 2019;Steinert et al, 2016).…”
Section: A Seamount Imprint On Sponge-associated Microbial Communitiesmentioning
confidence: 97%
“…Marine sponges [1,2] contribute significantly to known chemical space [3], accounting for nearly 30% of all specialized metabolites (SMs) reported from the marine environment [1,4]. It is also increasingly apparent that microorganisms play an important role in shaping the chemical space of the sponge holobiont [5,6].…”
Section: Introductionmentioning
confidence: 99%